An Inequality for Functions on the Hamming Cube. (29th March 2017) - SAMORODNITSKY, ALEX
Abstract : We prove an inequality for functions on the discrete cube 0, 1 n extending the edge-isoperimetric inequality for sets. This inequality turns out to be equivalent to the following claim about random walks on the cube: subcubes maximize 'mean first exit time' among all subsets of the cube of the same cardinality.